Fenomena Fatherless dari Sudut Pandang Wellbeing Remaja (Sebuah Studi Fenomenologi) - Vidya Nindhita; Elga Arisetya Pringgadani (Cakrawala - Jurnal Humaniora, 2023)
The emergence of the fatherless phenomenon is often due to a parenting paradigm that is influenced by patriarchal culture. Where it is said that the process of taking care of children is borne by the mother and fathers should not take care of children or be involved in parenting. The impact of fatherless will be different at each stage of the age of the child left behind, especially closely related to subjective well-being and especially in adolescents who are in a crucial period in their developmental stages. This study aims to find out how the description of subjective well-being in fatherless adolescents? The research uses qualitative research methods using semi-structured interviews and observation. Informants in this study are adolescents aged 15-18 years with the characteristics of adolescents from fatherless families. The results of this study state that the description of subjective well-being in fatherless adolescents is known in the affective component characterized by the presence of various kinds of negative and positive emotions related to the fatherless experiences they experience. In addition, the cognitive life evaluation component is characterized by global satisfaction and domain-specific satisfaction. The involvement of the role of father figures in the family is able to help assist adolescents in their crucial periods, especially in the affective aspect in the form of positive emotions and life satisfaction.